Internet infrastructure networking, web services, and cloud computing - Fox, Richard; Hao, Wei (CRC Press, Taylor & Francis Group, 2018)
Internet Infrastructure: Networking, Web Services, and Cloud Computing provides a comprehensive introduction to networks and the Internet from several perspectives: the underlying media, the protocols, the hardware, the servers, and their uses. The book covers in detail the Bind DNS name server, the Apache web server, and the Squid proxy server. It also provides background on those servers by discussing DNS, DHCP, HTTP, HTTPS, digital certificates and encryption, web caches, and the variety of protocols that support web caching.